Theoretical and Experimental Analysis of Drying Various Geometrical Forms of Red Pepper - (:unkn) unknown (POLISH ACAD SCIENCES INST PHYSICS, 2015)
In this study, a counter flow convection-type dryer was designed and manufactured. During experiments, four different geometrical forms of pepper specimens were dried in a complete (unsliced), perforated, crosscut, and longitudinally sliced forms. For each type of red pepper specimens, the experiments have been conducted at air velocity level of 0.5 m/s, relative humidity of 10-15%, and temperature of 55-60 degrees C. The theoretical mathematical model of drying process was developed, considering the pepper's bottom surface to be isolated. The drying curves of experimental results are compared to ones obtained from the theoretical analyses. The comparison showed that experimental results are consistent with the theoretical model. The best results, considering the drying duration, are collected from the specimens sliced longitudinally, which were followed by the crosscut specimens, perforated and unsliced-complete specimens, respectively. 82% water (humidity) content in 500 g sample was reduced to 4% in longitudinally cut samples, 6% in crosscut samples, 7.5% in perforated samples and 8% in unsliced-complete samples, after 14 hours of drying. It is suggested that regarding to easiness of processing, the crosscut red peppers are more suitable, compared to the other geometrical forms.
Keywords: BELL PEPPER; KINETICS